Vidusskolēna kultūrkompetences veidošanās kultūras vēstures mācību procesā - Avotiņa, Austra (Latvijas Universitāte, 2011)
Promocijas darba mērķis ir analizēt kultūras vēstures saturu vidusskolēna kultūrkompetences veidošanā, izvērtēt ieviesto "Kultūras vēstures" priekšmeta metodiku un formulēt izpētes rezultātus kā ieteikumus kultūrkompetences pilnveidei. Pētījumā ir trīs daļas, kurās apkopots jēdzienu kompetence, humānisms un kultūra zinātnisks skaidrojums, izveidota kultūrkompetences definīcija, veikta "Kultūras vēstures" mācību prirekšmeta teorētiskā analīze un izstrādāti vidusskolas līmeņa kultūrkompetences vērtējuma kritēriji un to indikatori. Rezultātā secināts, ka izstrādātie kritēriji ir praktiski izmantojami un ka piedāvātais saturs ir vidusskolas izglītības līmenim atbilstošs mācību modelis kultūrkompetences, kā integrētas personības īpašības ar mūžilgu vērtību, pilnveidei. Kultūrkompetence; kultūras vēsture; vidusskolas mācību process

Development of secondary school student’s cultural competence during studies of History of Culture The purpose of the thesis is to analyze the impact of the subject History of Culture on the development of secondary school students’ cultural competence. In addition the thesis analyzes the implemented methodology of the subject History of Culture and defines research results as suggestions for the improvement of the cultural competence. The thesis consists of three parts, where the scientific concepts of competence, humanism and culture are summarized; there is given the definition of cultural competence; there is carried out a theoretical analysis of the the subject History of Culture and there are developed evaluation criteria and indicators for cultural competence in secondary schools. As a result, it is concluded that the developed criteria are practically applicable and that the offered content is a corresponding learning model of the cultural competence for the educational level of secondary education to establish it as a personal quality of lifelong improvement. Cultural competence; History of Culture; secondary school study process
Development of secondary school student’s cultural competence during studies of History of Culture
Elektroniskā versija nesatur pielikumus
Keywords: Pedagoģija; Izglītība, pedagoģija un sports